Effectiveness and safety of an abacavir/lamivudine + rilpivirine regimen for the treatment of HIV-1 infection in naive patients. (2nd September 2016) - Curran, Adrian; Rojas, Jhon; Cabello, Alfonso; Troya, Jesús; Imaz, Arkaitz; Domingo, Pere; Martinez, Esteban; Ryan, Pablo; Górgolas, Miguel; Podzamczer, Daniel; Knobel, Hernando; Gutiérrez, Félix; et al.
Abstract : Objectives: To describe the effectiveness and safety of an abacavir/lamivudine + rilpivirine regimen in naive HIV-1-infected patients, as there is a lack of data with this combination. Methods: This was an observational, retrospective, multicentre study in eight Spanish hospitals. All antiretroviral-naive patients ≥18 years old and starting abacavir/lamivudine + rilpivirine were included. Effectiveness (ITT and on-treatment) and safety (adverse events and laboratory parameters) were assessed during follow-up. Values are expressed as n (%) or median (IQR). The Wilcoxon signed-rank test was used to compare baseline and 6 and 12 month values. Results: Eighty-four patients were included [93% males, age = 36 (30–45) years]. Time since HIV diagnosis was 12 (4–35) months. Fifty-one per cent of patients had comorbidities. Baseline CD4+ was 425 (340–519) cells/mm 3 and baseline HIV-RNA was 19 000 (9500–42 000) copies/mL. Median follow-up was 18 (9–22) months; 100% and 68% patients with at least 6 and 12 months, respectively. At 6 and 12 months effectiveness was 94% and 86% by ITT analysis and 96% and 97% by on-treatment analysis. At 12 months, there were significant increases in CD4+ (+262 cell/mm 3 ) and HDL cholesterol (+4 mg/dL) and a significant decrease in the total cholesterol/HDL cholesterol ratio (−0.2). There were two (2.4%) virological failures (HIV-RNA 50–100 copies/mL); one patient later achieving virological suppression without changing the treatment. Six patients (7.1%) changed treatment due to reasons other than virological failure or side effects. One patient discontinued treatment due to gastrointestinal complaints attributed to abacavir/lamivudine. Conclusions: Abacavir/lamivudine + rilpivirine was an effective and safe option in a selected group of HIV-1-infected treatment-naive patients.